Peningkatan kemampuan menyelesaikan soal cerita penyajian data melalui model teams gimes tournament (tgt) peserta didik kelas v sekolah dasar - Lucky Dwi Fitriani; Hadi Mulyono; Hadiyah Hadiyah (Didaktika Dwija Indria, 2019)
The purpose of research design was to increase the capability solve the story problem of presenting data by appliying the TGT learning model. Two cycles was used in this research design amount teacher and student 5th grade of primary school of SD N Mangkuyudan Surakarta conduct 30 students as the subject research. The data collecting techniques were test, observation, interview, and documentation. And the analyze data used a modified learning model with activities carried out outside the classroom. The first cycle result is of 50% for classical and result of second cycle is a 83,33% for classical. The conclusion is applying TGT model activities can work up the capability solve the story problem of presenting data in the fifth grade of SD N Mangkuyudan Surakarta in the 2018/2019.